Investigation of in-nozzle flow behavior coupled with spray characteristics of waste cooking oil and castor biodiesel - Muteeb ul Haq; Ali Turab Jafry; Wajahat Ullah Khan; Arslan Ahmed; Muhammad Abdul Ahad; Sattar Jabbar Murad Algayyim; Naseem Abbas; Uzair Sajjad; Khalid Hamid (Energy Conversion and Management: X)
Biodiesel is a promising alternative to conventional diesel. However, it may cause reduced mass flow, higher injector deposits and poor atomization. This study presents the numerical investigation of the effect of in-nozzle flow on fuel spray behavior for castor methyl ester (CME20) and waste cooking oil methyl ester (WCME20) using two different nozzle hole sizes. Two step simulation methodology was adopted where flow inside the nozzle was simulated first, mass flow rate and velocities at nozzle outlet were used as an input for analyzing the fuel spray in a closed vessel. These simulated results of fuel spray were also validated with experimental results from the captured spray images from control volume spray vessel (CVSV). Experimental spray results were also investigated based on light intensity level and macroscopic spray properties. Results revealed higher cavitation intensity for diesel than biodiesel fuels. Smaller nozzle hole (N2) is more likely to cavitate as compared to larger nozzle diameter (N1). In terms of spray behavior, N1 nozzle on average showed longer penetration length (+1.95 %), wider spray cone angle (+6.2 %) and larger drop diameter (+3.1 %) in comparison to N2. CME20, due to its increased viscosity and density showed longer penetration length (+5.9 %), narrower spray cone angle (−21 %) and reduced spray projected area (−19 %) with respect to diesel. WCME20 revealed smaller sauter mean diameter (−4.8 %) as compared to CME20 owing to its lower viscosity.